2010
DOI: 10.4314/bajopas.v3i1.58748
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for setting dose reference level for medical radiography in Nigeria: a review

Abstract: Patients' dose audit reports in some Nigerian hospitals had shown large inter-and intra-hospital variations for the same radiological examinations. They have thus presented the need, to have a national standard for radiological diagnostic procedures and set dose limits for individual x-ray examination centers in Nigeria. These will go a long way in reducing inter-and intra-hospital dose range factors, thus reducing doses to as low as reasonably achievable and consistent with clinical objectives of the examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Research has shown that the difference between the minimum dose in one diagnostic center and the maximum dose in another can be up to 50 times as much [ 3 ]. Taking into account the principle of optimization, and having found these inconsistencies, the term "Diagnostic Reference Value" was proposed in 1990 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the difference between the minimum dose in one diagnostic center and the maximum dose in another can be up to 50 times as much [ 3 ]. Taking into account the principle of optimization, and having found these inconsistencies, the term "Diagnostic Reference Value" was proposed in 1990 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However the FAE at the point where the X-ray central beam measures strike the body may be measured using ionization chamber. [4], [20], [26], [27].…”
Section: Measuring Free Air Exposure (Fae)mentioning
confidence: 99%
“…Despite the attractive nature of the calculation methods of patient dose, one should make sure that the used x-ray equipment has an adequate QC protocol that ensures the accuracy of the measured factors [16,17,20] . Although, ESD may be sufficient for quality control measurements where the stability of the x-ray equipment is often of concern, the entrance dose is not sufficient for comparison or evaluation of actual patient dose and associated risk [16,25] . The objective of this study is to estimate and assess ESD and image quality of chest x-ray examinations and to use it as a standard in determining an easier method in assessing reference dose compliance criteria of patient's radiation exposure to medical x-rays in the hospitals within this region.…”
Section: Assessment Of Entrance Skin Dose and Image Quality Of Chest mentioning
confidence: 99%